Comparing the analytical performance of near and mid infrared spectrometers for evaluating pomegranate juice quality. (May 2018) - Arendse, Ebrahiema; Fawole, Olaniyi Amos; Magwaza, Lembe Samukelo; Nieuwoudt, Helene; Opara, Umezuruike Linus
Abstract: Near infrared (NIR) and mid infrared (MIR) spectral acquisition modes were compared for predicting organoleptic and phytochemical quality attributes of pomegranate juice. Three Fourier transform infrared (FT-IR) spectrometers namely, a FT-NIR spectrometer, FT-MIR spectrometer in attenuated total reflection mode and FT-MIR spectrometer in transmission mode were used. Calibration models were constructed by subjecting the spectral data to partial least squares regression analysis. The models were assessed based on their overall performance (lower root mean square error of prediction, the number of latent variables and residual predictive deviation). The predictive abilities of the instruments for juice quality attributes were statistically compared using Bland and Altman, and Passing-Bablok. The outcomes are critically discussed, which showed the suitability of the FT-MIR spectrometer in transmission mode for predicting selected quality attributes of pomegranate juice. Highlights: The analytical performance of three FT-IR spectrometric methods were investigated. Organoleptic and phytochemical parameters were evaluated. Statistical analysis suggest the three instruments were not significantly different. The WineScan spectrometer were found suitable for evaluation of selected parameters.